Study on “Triaxial Loading-Unloading-Uniaxial Loading” and Microscopic Damage Test of Sandstone - Yuan, Chao; Guo, Yuning; Wang, Wenjun; Cao, Liming; Fan, Lei; Huang, Cong (Frontiers in Earth Science, 2020)
To study the weakening process, deformation, and failure characteristics of rock masses surrounding deep chambers under complex stress environments, triaxial loading tests along with triaxial loading/unloading followed by uniaxial loading tests were conducted on sandstone specimens. The internal microcracks of the specimens under the loading and unloading of triaxial confining pressure were observed by scanning electron microscopy. The results revealed the inherent mechanism of plastic deformation (irreversible deformation) of the rock mass under different confining pressures. Under uniaxial loading and triaxial loading, the sandstone specimens exhibited X-shaped shear failure and single shear failure, respectively. In contrast, the sandstone samples subjected to the loading and unloading of triaxial confining pressure followed by uniaxial loading showed multiple shear fracture surfaces and fine fissures along the axial direction. A larger initial axial pressure of the sandstone specimen corresponded to a smaller uniaxial loading strength after unloading the confining pressure, a greater amount of plastic deformation, more macro- and microfissures, and more severe damage to the specimen. These results show that the final failure mode, strength, degree of damage, and plastic deformation of sandstone specimens are related to the stress state at the time of failure along with the loading history before failure.